Greenland subglacial lakes detected by radar. Issue 23 (9th December 2013) - Palmer, Steven J.; Dowdeswell, Julian A.; Christoffersen, Poul; Young, Duncan A.; Blankenship, Donald D.; Greenbaum, Jamin S.; Benham, Toby; Bamber, Jonathan; Siegert, Martin J.
Abstract [1] Subglacial lakes are an established and important component of the basal hydrological system of the Antarctic ice sheets, but none have been reported from Greenland. Here we present airborne radio echo sounder (RES) measurements that provide the first clear evidence for the existence of subglacial lakes in Greenland. Two lakes, with areas 8 and 10 km2, are found in the northwest sector of the ice sheet, 40 km from the ice margin, and below 757 and 809 m of ice, respectively. The setting of the Greenland lakes differs from those of Antarctic subglacial lakes, being beneath relatively thin and cold ice, pointing to a fundamental difference in their nature and genesis. Possibilities that the lakes consist of either ancient saline water in a closed system or are part of a fresh, modern open hydrological system are discussed, with the latter interpretation considered more likely.